Carotenoid comparison among broccoli leaves, stems, and flowers dried with drying cabinet - Devi Mazarina; Soekopitojo Soenar; Wibawa Aji Prasetya; Nusa Cassandra Permata; Pratiwi Zahra Anggita (BIO Web of Conferences)
Vegetables are essential for humanity due to their colour, taste, nutrition, and health. Carotene, a vitamin A precursor and a potent antioxidant, is one of the essential nutrients present in vegetables. The present work was initiated to study the carotenoid content in Broccoli plants dried by cabinet dryer with emphasis on the carotenoid distribution of β- carotene, α-carotene, phytofluene, phytoene and lutein in the leaves, stems and flowers of the plant. These compounds were quantified with the help of High-Performance Liquid Chromatography (HPLC). Based on the results, the highest amount of carotenoids histologically present was found in the broccoli leaves, particularly in β-carotene 131.51 μg/g, which was more than in the stems 77.52 μg/g and flowers 55.24 μg/g. One-way ANOVA analysis of variance was carried out. The results were significant in carotenoid content of leaves, stems and flowers p < 0.05, except for phytoene, where no significant difference was noted. It can be concluded that the broccoli leaves, which are usually discarded, are an excellent source of nutrients and therefore can be incorporated into food formulations, especially in the formulations meant to boost antioxidant and provitamin A levels. This study lays down the foundation for improving food processing methods for the better nutritional quality of dry vegetables and sheds light on using Broccoli leaves to achieve sustainable food production by reducing food waste.